Single and Investing: Homeownership Trends among the Never Married - Kusum Mundra; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2016)
In recent years, singles have begun to take on a more prominent role in reshaping America. As a group, singles are increasingly becoming influential in politics and in the determination of many macro socioeconomic outcomes. In this descriptive paper we focus on homeownership among a subset of singles, the never married. In particular we investigate potential differences in the relationship between several homeownership determinants for singles in comparison to the married. In addition, we test for heterogeneity across race and skill level in the gender gap in homeownership and the probability of homeownership before and post the recession. Our results suggest that there are some differences in the relationship between certain factors and homeownership for singles versus those who are married. In particular, we find age, gender, and number of children affect the probability of homeownership differently for singles compared to those who are married. We also find that while on average there is a higher probability of homeownership from 2007 onwards for singles, there are gender, education and racial differences. Our results also suggest significant heterogeneity across race and skill level in homeownership probabilities for singles.
Keywords: J10; J11; D10; 330; homeownership; single; ethnicity; gender; race; recession